COMPARISON OF TWO METHODS FOR TREATMENT OF RETAINED FETAL MEMBRANES IN CROSSBRED COWS IN RURAL CONDITIONS - KRISHNA, K MOULI (The Indian Journal of Animal Reproduction, 2023)
A total of 17 crossbred cows suffering with retained fetal membranes (RFM) were randomly divided into two unequal groups. The cows in Group I and II were assigned to manual removal and non-removal of RFM, respectively. The average time interval for complete uterine involution was 35. 71 ± 1.06 and 33.2 ± 0.81 days in Group I and 11, respectively.